Analyzing Construction Risk Factors in Large-Scale Projects: Case Study on the Suramadu Bridge - Reinaldy Jastino; Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2024)
This study aims to comprehensively examine the risk management practices, challenges, and strategies employed during the construction of the Suramadu Bridge. A structured data collection process began with defining clear objectives to identify risks related to structural integrity, environmental impacts, financial uncertainties, project delays, and safety concerns. Key search terms such as "Suramadu Bridge construction," "risk management in bridge construction," and "construction risk assessment" guided searches across reputable online databases like Google Scholar, IEEE Xplore, ScienceDirect, the ASCE Library, JSTOR, and SpringerLink. Articles were selected based on relevance, credibility, publication date, and analytical depth. Data from these articles were extracted and organized, documenting metadata, key points, risk types, and mitigation strategies. The synthesized data revealed common themes and unique insights into the risk management practices during the Suramadu Bridge construction. The discussion delved into these themes, comparing and contrasting different risk management strategies from the literature. Key findings included effective mitigation strategies for financial and environmental risks, the importance of early risk assessment, and the role of continuous monitoring. Challenges in managing these risks were analyzed, showing how they were overcome or mitigated. The report concluded with recommendations for future infrastructure projects, emphasizing a systematic and proactive approach to risk management. Utilizing tools such as Zotero for reference management, Excel for data organization, and Microsoft Word for report compilation ensured efficiency and accuracy. This approach provided valuable insights into risk management for large infrastructure projects, offering a robust foundation for future research and practice.